KAJIAN FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEBERHASILAN KELOMPOK TANI SEBAGAI UNIT USAHA/BISNIS - Sunarru Samsi Hariadi (Agro Ekonomi, 2004)
In Indonesia, the activity of agricultural development is very much emphasized through the effort of human resources (HR) empowerment, in which this effort is done through agricultural extension including farmer group approach. In 1993, Martaatmadja (1993) recorded that there were 250,000 farmer groups in Indonesia, but the only active ones were 20 percent of them. In 2000, in Gunungkidul Regency , it was recorded that there were 1446 farmer groups, in which the active ones are for instance the main class as calculated to be about 10.46 percent . Active farmer groups which were able success in the activity of business unit less than 10 percent.This research is meant to study the factors influencing the successs of farmer groups as business unit. The research was done in Gunungkidul Regency by using the method of survey, with groups as its unit of analysis, and there were 90 farmer groups as sample taken by the method of Stratified Random Sampling. Each group was represented by 5 members taken randomly as group representatives, including 1 member of the board (no the chairman), 2 developed/ active farmers, and 2 regular/ less active farmers. The resulting data of the research were analysed using multiple regression, using computer program of SPSS. Then, analysis was developed through path analysis, using computer program ofAmos.The result of this research shows that factors influencing the success farmer groups as business unit were: self efficacy ofmembers of groups, interaction among members, and leadership style of chairman of groups.The success of groups as business units generally evidenced in middle and main class offarmer groups, with the conduct of certain activities: agricultural equipment rental (sprayer, diesel water pump machine, etc), stalls owned by group, cooperatives owned by groups, livestock/ fisheries owned by groups, partnership with companies, etc.